Jak uczyć grać innych, nie gubiąc własnych nut. Wybrane zasoby osobiste a zespół wypalenia zawodowego u muzyków klasycznych - Chanduszko-Salska, Jolanta; Młynarczyk, Anna (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
Stress in the workplace, personal resources and professional burnout concern many workers in the contemporary world. These are common problems also among two groups of musicians: teaching musician and non-teaching musicians. The purpose of the study was to establish the dependence between occupational stress and burnout syndrome in these groups. The studied groups consisted of 94 musicians. The Perceived Job Stress Questionnaire, Maslach Burnout Inventory, Generalized Self- Efficacy Scale, The Resiliency Assessment Scale were used in this study. The data obtained revealed significant differentiation in a level of stress in the workplace among teaching musicians and non- teaching musicians. Teaching musicians differs in comparison with non-teaching musicians in general level of stress and four its factors: psychical balance of work, lack of rewards, social contacts and uncertainty at work. The data obtained revealed significant intensity of stress feeling at work in evaluated group. However, there are no significant differences in personal resources. To conclude: higher intensity of occupational stress is connected with the greater intensification of burnout syndrome and lower intensification of sense of personal achievements in investigated group of teaching musicians.